Dispute Settlement of International Trademark on Intellectual Property Rights (Case Study: Decision Number 557 K/PDT.SUS-HKI/2016) - Arkianti Anindita Putri; Dewi Ratnadewanti; Kamila Khaerunisa; Sheikha Dwi Nabilla; Nadia Rastika Alam; Mustika Mega Wijaya (Universitas PGRI Madiun, 2024)
Intellectual Property Rights (IPR), namely rights resulting from the impact of thought patterns resulting in products that are beneficial to legal subjects. However, there are still many problems that arise in IPR such as brand theft, brand plagiarism and so on. One of them is the case of Laverana, a cosmetic product from Germany. This brand was plagiarized by Irawan Gunawan to be used as a product brand in Indonesia. On top of these things, Laverana also felt disadvantaged. Therefore, this article aims to provide an understanding of the importance of protecting IPR and how to resolve international trademark disputes. The research method used in this research itself is a normative-empirical legal research method and a literature approach as well as legal protection theory and effectiveness theory in this brand plagiarism dispute case. The resolution of the Intellectual Property Rights dispute in the Laverana case was pursued through litigation, namely the Indonesian court to try the defendant, namely Irawan Gunawan. The final decision obtained from the court stated that the party from Germany or the original owner of the Laverana Brand won. This resulted in Irawan Gunawan (defendant) having to withdraw from the brand and being charged legal fees of Rp. 5,000,000 (5 Million Rupiah).